2017
DOI: 10.15544/mts.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Servitization of Lithuanian Agricultural Cooperatives

Abstract: To survive and be competitive in the changing economic environment, agricultural cooperatives are innovating and creating more sophisticated, added-value products and broadening the range of provided services. Lithuanian cooperatives, facing the same challenges, are less flexible and adaptable to changes due to short operational history and sparse membership. Therefore, the following scientific problem is addressed: do Lithuanian agricultural cooperatives still represent a shift to servitizing? The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…van Oorschot et al (2013) suggested that the investigation and examination of cooperatives in different countries might be beneficial because the findings of each research are contributions to the knowledge of the field as a whole and that the results obtained from the study of cooperatives in different countries might help to develop better theories and plans of cooperatives. Šumylė and Ribašauskienė (2017) suggested that further efforts should be addressed towards identifying the causes and barriers for more successful performance among cooperatives. Amene (2017) suggested that future research may make an in-depth study by considering other regions to clearly factors influencing agricultural cooperatives’ performance.…”
Section: Introductionmentioning
confidence: 99%
“…van Oorschot et al (2013) suggested that the investigation and examination of cooperatives in different countries might be beneficial because the findings of each research are contributions to the knowledge of the field as a whole and that the results obtained from the study of cooperatives in different countries might help to develop better theories and plans of cooperatives. Šumylė and Ribašauskienė (2017) suggested that further efforts should be addressed towards identifying the causes and barriers for more successful performance among cooperatives. Amene (2017) suggested that future research may make an in-depth study by considering other regions to clearly factors influencing agricultural cooperatives’ performance.…”
Section: Introductionmentioning
confidence: 99%